REPORT OF METEOROLOGY, THE JAPANESE ANTARCTIC RESEARCH EXPEDITION VI, 1961-62 - Narimasa TAJIMA (National Institute of Polar Research, 1963)
In the 6th Japanese Antarctic Research Expedition in 1961-1962, meteorological section on board m/s "SOYA", consisting of 3 meteorologists, carried out the following observations. a) Maritime surface observations: 8 times daily b) Making surface and upper air charts: once daily c) Weather forecasts and briefing for ship: daily basis Besides, radiosonde observations were also taken by 6th expedition members not on routine basis. At Syowa Base, during cartographical operations by aircraft, weather forecasting works had been kept, in addition to surface and pilot balloon observations by the 5th and 6th expedition members. During the transportation periods by helicopter flights, the forecasting operations were also continued on board ship. The weather conditions over around Lutzow-Holm Bay were so bad this year that operations, of air transportation and of ship's ice breaking in pack ice areas were considerably obstructed. Major reasons for this were mainly considered as follows: 1) Expansion of the polar-cap anticyclone over Queen Maud Land and Enderby Land were so weak that the successive invasions of warmair were maintained. It is subsequently indicated that the antarctic fronts near the coastal region of the continent were very active throughout the period. 2) As there were so many occasions on which the ridges of long wave were located on the area farther east than 50°E and the troughs at about 40°E or farther west, the blowing of predominant E-ly winds which would give a significant influence on both weather and ice conditions had been continued.